MALDI-ion mobility-TOFMS imaging of lipids in rat brain tissue - Jackson, Shelley N. (2007)
While maintaining anatomical integrity, matrix assisted laser desorption/ionization mass spectrometry (MALDI-MS) has allowed researchers to directly probe tissue, map the distribution of analytes and elucidate molecular structure with minimal preparation. MALDI-ion mobility (IM)-orthogonal time-of-flight mass spectrometry (oTOFMS) provides an advantage by initially separating different classes of biomolecules such as lipids, peptides, and nucleotides by their IM drift times prior to mass analysis. In the present work the distribution of phosphatidlycholine and cerebroside species was mapped from 16 μm thick coronal rat brain sections using MALDI-IM-oTOFMS. Furthermore, the use of gold nanoparticles as a matrix enables detection of cerebrosides, which although highly concentrated in brain tissue, are not easily observed as positive ions because of intense signals from lipids such as phosphatidlycholines and sphingomyelins.